Container volume and shading in Parkia multijuga Benth. propagation in nursery - Maekawa, Luiz; Coelho, Maria de Fatima Barbosa; Weber, Oscarlina Lúcia dos Santos (Iheringia, Série Botânica., 2020)
Parkia multijuca Benth. is one of the Forest species that occurs in the Amazon region. The aim of the this study was evaluate the development of seedlings of Parkia multijuga in differents shading and container volume in nursery. The experimental design was a randomized block design in 4 x 4 subplotplot (4 shadings and 4 containers volumes). The shading was 0, 30, 50 and 70% and containerv olumes 110, 180, 290 and 400 cm³. The diameter, root drymass, shootdrymass, total dry mass and the Dickson quality índex of the seedlings increased proportionally with container volume and with the availability of light. The conduction of the seedlings in full sun and container volume 400 cm³ favors the development of P. multijuga quality seedlings and 70% shading should not be used in nurseries to produce P. multijuga seedlings.